RP-HPLC Method for Simultaneously Quantifying the Antiviral Drug Contents of Acyclovir, Amantadine, and Oseltamivir in Pharmaceutical Formulations - Ahmed, Sohair Salah; Rasheed, Ashraf Saad (Iraqi Journal of Science, 2024)
Antibiotics treat bacterial infections, whereas antiviral drugs treat viral illnesses. Antivirals are used to treat a variety of infectious diseases, including COVID-19 and influenza. The technique of reversed-phase high-performance liquid chromatography (RP-HPLC) provides more sensitivity and precision than other approaches, particularly spectrophotometric. This research seeks to develop a simple method for simultaneously quantifying acyclovir, amantadine, and oseltamivir in creams and capsules. The RP-HPLC method optimization and development for verifying the separation and quantification of three antiviral drugs included the investigation of the optimal buffer concentration, pH value, and acetonitrile content. On a C8 HyperClone BDS column, the RP-HPLC system with UV detection achieved separation (250 x 4.60 mm, 130A, and 5). The mixture of acetonitrile and acetate buffer as mobile phase gradient elution at a detection wavelength of 254 nm and 1 mL/min flow rate. The proposed method provided a linear range of 0.08-10.5, 0.06-4.5 and 0.02-14 μg/mL, as well as excellent validated values for LOD (0.0205, 0.0107, and 0.0083 μg/mL) and LOQ (0.0621, 0.0324 and 0.0251 μg/mL) with a coefficient of determination (r2) of the regression line of 0.9998, 0.9988, and 0.9994 for acyclovir, amantadine, and oseltamivir, respectively.